TINDAK TUTUR DALAM UPACARA PERNIKAHAN MASYARAKAT MADURA DI DESA KALIDANDAN, PAKUNIRAN, PROBOLINGGO: KAJIAN PRAGMATIK - AAN Anwari (Program Magister Linguistik Universitas Udayana, 2017)
Speech act is language use which considered as the system of communication in speech done by people on certain situations. Speech act can be stated as the essence of language use related to physical component and psychological language self. It is a deliberacy to make interpretations on what would like to say, for instance speech wedding ceremony done by Madurese at Kalidandan village, Pakuniran district, Probolinggo regency had some phases, those are phase of engagement, pre-wedding, marriage, and post wedding. This research used qualitative descriptive approach with listening method (observation method). The theory used in this research is theory pragmatics. The analysis results stated that illocutionary act at speech act of madurese wedding ceremony at Kalidandan, Pakuniran, Probolinggo are concluded (1) asking, (2) do not play around in marriage, (3) grateful, (4) regret, (5) willingly, (6) patient, (7) time of scarcity before harvesting, and (8) pregnant under married. Meanwhile, it found part of speech act (1) direct speech act, (2) indirect speech act, (3) literal speech act, (4) nonliteral speech act, (5) direct literal speech act, (6) indirect speech act, (7) direct nonliteral speech act, and (8) indirect nonliteral speech act.